The Influence of Attitude, Clarity Of Information, and Credibility on the Repurchase Intention of Wardah Lipstick in the City of Bandung - Saskia Putri Brilian; Abdul Ahmad Hafidh Nurmansyah (LP2M IAIN Palopo, 2026)
Indonesia's cosmetics industry has experienced significant growth in recent years, accompanied by increasingly fierce competition between local and international brands. Wardah, as one of the leading halal cosmetics brands in Indonesia, has managed to build a strong market presence through its commitment to halal certification, product quality, and affordable prices. However, the latest Top Brand Index data shows a continued decline in the performance of Wardah's lipstick market, which indicates a decline in consumer repurchase intentions. This situation highlights the importance of identifying the factors that influence consumers' desire to repurchase cosmetic products. This study aims to examine the influence of attitudes, clarity of information, and credibility on the intention to repurchase Wardah lipstick among consumers in the city of Bandung. A quantitative research approach with a verifiable design is used. Primary data was collected through a questionnaire distributed to 150 consumers aged at least 17 years who had previously purchased Wardah lipstick. Data were analyzed using multiple linear regression with the help of IBM SPSS Statistics Version 26. The results show that consumers generally perceive attitudes, clarity of information, credibility, and repurchase intentions positively. The results of the hypothesis test revealed that attitude did not have a significant positive effect on repurchase intention, while clarity of information and credibility had a positive and significant effect on repurchase intention. Furthermore, simultaneous analysis showed that attitude, clarity of information and credibility had a positive and significant effect on the repurchase intention of Wardah lipstick in the city of Bandung.